A macroeconomic model of the term structure of interest rates in Mexico - Josué Fernando Cortés Espada; Manuel Ramos-Francia (Banco de México, 2008)
This paper investigates how different macroeconomic shocks affect the term-structure of interest rates in Mexico. In particular, we develop a model that combines a no-arbitrage specification of the term structure with a macroeconomic model of a small open economy. We find that shocks that are perceived to have a persistent effect on inflation affect the level of the yield curve. The effect on medium and long-term yields results from the increase in expected future short rates and in risk premia. With respect to demand shocks, our results show that a positive shock leads to an upward flattening shift in the yield curve. The flattening of the curve is explained by both the monetary policy response and the time-varying term premia.
Keywords: C13; E43; G12; 330; Term-Structure; No-Arbitrage; Macroeconomic Shocks; Zinsstruktur; Mexiko